Thankful, Always Thankful - Valdez, Ria (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
This shorty story is about Manang Neng, a street food vendor who is struggling with the COVID-19 protocols of a public market in Davao City. While her only wish is to have her daughter Julie take over their street food business during the pandemic, Julie refuses to do so as she wants to finish her studies.